Wireless mobile communications at the start of the 21st century. - Qi Bi (IEEE Communications magazine)
At the start of the 21st century, the wireless mobile markets are witnessing unprecedented growth fueled by an information explosion and a technology revolution. In the radio frequency arena, the trend is to move from narrowband to wideband with a family of standards tailored to a variety of application needs. Many enabling technologies including wideband code-division multiple access, software-defined radio, intelligent antennas, and digital processing devices are greatly improving the spectral efficiency of third-generation systems. In the mobile network area, the trend is to move from traditional circuit-switched systems to packet-switched programmable networks that integrate both voice and packet services, and eventually evolve toward an all-IP network. Furthermore, accompanied by wireless mobile location technology, wireless mobile Internet is expected to revolutionize the services that can be provided to consumers in the right place and at the right time. Wireless mobile communications may not only complement the well established wireline network; it may also become a serious competitor in years to come. We review the history of the wireless mobile communications, examine the current progress in standards and technologies, and discuss possible trends for wireless mobile solutions